2011
DOI: 10.1165/rcmb.2010-0179oc
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin Receptor ErbB4 Functions as a Transcriptional Cofactor for the Expression of Surfactant Protein B in the Fetal Lung

Abstract: Sufficient pulmonary surfactant production is required for the fetalneonatal transition, especially in preterm infants. Neuregulin (NRG) and its transmembrane receptor ErbB4 positively regulate the onset of fetal surfactant synthesis. Details of this signaling process remain to be elucidated. ErbB4 is known to regulate gene expression in the mammary gland, where the receptor associates with the signal transducer and activator of transcription Stat5a to transactivate the b-casein gene promoter. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…Interestingly, there is a genetic correlation between ErbB-4 and schizophrenia (Pan et al 2011) and the involvement of the ICD fragment in controlling gene expression in relevant cell types has been reported (Wong and Weickert 2009;Allison et al 2011). Also, the maturation of fetal lung cells is reported to be dependent on secretase processing of ErbB-4 and ICD association with the transcription factors YAP (Hoeing et al 2011), STAT 5a (Zscheppang et al 2011a), and ERb (Zscheppang et al 2011b). It is suggested that these interactions allow ErbB-4 to regulate transcription of surfactant protein B and thereby promote lung maturation.…”
Section: Secretase Processing Of Rtks Erbb-4 Receptormentioning
confidence: 99%
“…Interestingly, there is a genetic correlation between ErbB-4 and schizophrenia (Pan et al 2011) and the involvement of the ICD fragment in controlling gene expression in relevant cell types has been reported (Wong and Weickert 2009;Allison et al 2011). Also, the maturation of fetal lung cells is reported to be dependent on secretase processing of ErbB-4 and ICD association with the transcription factors YAP (Hoeing et al 2011), STAT 5a (Zscheppang et al 2011a), and ERb (Zscheppang et al 2011b). It is suggested that these interactions allow ErbB-4 to regulate transcription of surfactant protein B and thereby promote lung maturation.…”
Section: Secretase Processing Of Rtks Erbb-4 Receptormentioning
confidence: 99%
“…In the lung, both TTF-1 and ErbB4 protein have important roles in promoting surfactant protein expression (Boggaram 2009;Zscheppang 2011). Our previous experiments in fetal murine ATII cells showed that there is an interaction between TTF-1 and ErbB4 (Zscheppang 2013).…”
Section: Discussionmentioning
confidence: 98%
“…To examine the effects of HER4 and Nkx2.1 (the genes encoding for ErbB4 and TTF-1) overexpression on SP-B, ErbB4, and TTF-1 protein expression levels, MLE-12 cells and primary fetal ATII cells were transfected with plasmid expressing human ErbB4 (HER4), or Nkx2.1, or an empty control construct (EGFP) (Zhou 2008;Zscheppang 2011Zscheppang , 2013. The MLE-12 cells were only transfected with Nkx2.1 or EGFP, since we have already published the effects of ErbB4 overexpression in MLE-12 cells on surfactant protein expression (Zscheppang 2013).…”
Section: Transfection Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fetal lung, HER4 activation promotes ATII proliferation (66) and fetal lung growth, and genetic deletion of HER4 results in hypoplastic lungs similar to those observed in bronchopulmonary dysplasia (67). Surfactant production, a key physiological function of ATII cells, is regulated by HER4 in the developing lung (66,68). Given these critical roles for HER receptors in pulmonary organogenesis, these pathways are likely to play important roles in the setting of ALI and repair.…”
Section: Her Signaling and Lung Developmentmentioning
confidence: 96%